NADPH Oxidase Signaling Pathway Mediates Mesenchymal Stem Cell-Induced Inhibition of Hepatic Stellate Cell Activation - Haowen Qiao; Yu Zhou; Xingping Qin; Jing Cheng; Yun He; Yugang Jiang (Hindawi Limited, 2018)
Background. Bone marrow-derived mesenchymal stem cells (BMSCs) have blossomed into an effective approach with great potential for the treatment of liver fibrosis. The aim of this study was to investigate the underlying antifibrosis mechanisms by which the BMSC inhibit activated hepatic stellate cells (HSCs) in vivo and in vitro. Methods. To study the effect of human bone marrow-derived mesenchymal stem cells (hBM-MSCs) on activated HSCs, we used HSCs and the coculture systems to evaluate the inhibition of activated HSCs from the aspects of the apoptosis of activated HSCs. In addition, activation of NADPH oxidase pathway and the changes in liver histopathology were tested by using the carbon tetrachloride- (CCl4-) induced liver fibrosis in mice. Results. Introduction of hBM-MSCs significantly inhibited the proliferation of activated HSCs by inducing the apoptosis process of activated HSCs. The effect of hBM-MSCs reduced the signaling pathway of NADPH oxidase in activated HSCs. Besides, the signaling pathway of NADPH oxidase mediated hBM-MSC upregulation of the expression of the peroxisome proliferator-activated receptor γ and downregulation of the expression of α1(I) collagen and alpha-smooth muscle actin (α-SMA) in activated HSCs. Moreover, the hBM-MSC-induced decrease in the signaling pathway of NADPH oxidase was accompanied by the decrease of the activated HSC number and liver fibrosis in a mouse model of CCl4-induced liver fibrosis. Conclusion. The hBM-MSCs act as a promising drug source against liver fibrosis development with respect to hepatopathy as a therapeutic target.